“…There Is Such Avant-Garde” - Uspenskaya, Olga (project baikal, 2019)
The educational project “…There Is Such Avant-Garde”, the ideologist and the curator of which is Olga Uspenskaya, head of the creative space “ArchiMY” (Krasnoyarsk), became one of the laureates of the International Architectural Festival “Zodchestvo 2018” and was awarded the Union of Architects of Russia Diploma. The main partner of the project is Eduard Kubensky, editor-in-chief of TATLIN Publishers (Yekaterinburg). The article presents the content and the events of the project.
Keywords: “ArchiMY”; educational project; Eduard Kubensky; avant-garde; creative policy; architecture; art of the XX century